2003
DOI: 10.1002/marc.200300023
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Epoxy–Amine Curing Accompanied by the Formation of Liquid Crystalline Structure

Abstract: The curing of a mesomorphic epoxy has been studied by polarized light microscopy (PLM) and differential scanning calorimetry. PLM in combination with wide‐angle X‐ray diffraction proves the formation of a liquid crystalline (LC) structure. An advanced isoconversional method reveals that the formation of the LC structure is accompanied by a dramatic decrease in the effective activation from ∼60 to ∼10 kJ · mol−1. A kinetic model of the phenomenon has been discussed.The dependence of the activation energy on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 17 publications
4
39
1
1
Order By: Relevance
“…The activation energy values obtained for both alachlor and metolachlor at the end of the vaporization are in close agreement with the enthalpies of vaporization calculated from DSC measurements. This result was also confirmed by several authors [25,26]. Additional XRD and FTIR measurements performed before and after the heating cycle show that metolachlor follows vaporization without decomposition, while a different behavior was observed for alachlor.…”
Section: Zero-order Kineticssupporting
confidence: 90%
See 1 more Smart Citation
“…The activation energy values obtained for both alachlor and metolachlor at the end of the vaporization are in close agreement with the enthalpies of vaporization calculated from DSC measurements. This result was also confirmed by several authors [25,26]. Additional XRD and FTIR measurements performed before and after the heating cycle show that metolachlor follows vaporization without decomposition, while a different behavior was observed for alachlor.…”
Section: Zero-order Kineticssupporting
confidence: 90%
“…Isoconversional methods have recently been used with success to describe the kinetics of physical transformations [23], and of chemical reactions complicated by physical transformations [24][25][26].…”
Section: Model-free Approachmentioning
confidence: 99%
“…Similar behaviour was observed for isothermal curing of epoxy-amine 29 0.07 1.93 Figure 5 Determination of E a for isothermal DSC cure of quasi-prepolymer and water, by applying the method of Friedman (a) and the integral method (b).…”
Section: Isothermal Dsc Methodssupporting
confidence: 69%
“…[20] Also the curing rates of DEPBP/DDM show an abnormal increase under medium conversion at 120 and 130 8C. The interesting phenomenon of this increase of curing rate was reported by most researchers in isothermal [1,11,15,21] or dynamic investigations. [19] However some researchers reported curing rate-conversion curves without abnormity from that of a cure of epoxy without mesogenic groups, which can be described by the Kamal 2228 G. Liu, J. Gao, L. Song, W. Hou, L. Zhang Figure 6.…”
Section: Curing Kineticsmentioning
confidence: 85%
“…[8][9][10] Even then, most studies showed that a liquid crystalline phase develops during curing despite the fact that the epoxy monomer or its mixture with hardener shows no mesophase. [3,[8][9][10][11][12] Thus, a mesophase may appear, independent of the properties of the dioxide monomer, if it has a mesogenic structure.…”
Section: Full Papermentioning
confidence: 99%